Stable estimates for source solution of critical fractal Burgers equation. (January 2016) - Jakubowski, Tomasz; Serafin, Grzegorz
Abstract: In this paper, we provide two-sided estimates for the source solution of d -dimensional critical fractal Burgers equation u t − Δ α / 2 + b ⋅ ∇ ( u | u | q ) = 0, q = ( α − 1 ) / d, α ∈ ( 1, 2 ), b ∈ R d, by the density function of the isotropic α -stable process.